SURNAME AS A DISTINCTIVE, IDENTIFICATION FACTOR AT THE PROSODIC LEVEL. HOW TO PRESERVE IT? - Stipe Kekez (Fluminensia: Journal for Philological Research, 2011)
The article deals with surnames as a distinctive, identification factor at the prosodic level. Surnames are distinctive at the prosodic level due to derivation and etymology. Therefore, they are not the same surnames, nor the variants thereof. It often happens that surnames which are equal at the segmental but different at the suprasegmental level modulate themselves to either the dominant type or to territorially, prestigious pronunciation. In the times when the formalization of diversity is emphasized in society, there is a question how to preserve that kind of diversity, which criterion to select and how to preserve such differences. The preservation can be stimulated in elementary school education and that could help in teaching accent.